TINDAKAN KRIMINALITAS REMAJA DI WILAYAH HUKUM POLSEK TAMPAN KOTA PEKANBARU (Studi Kasus Tindak Pidana Penganiayaan dan Pengeroyokan) - Fazarina, Nurul; Kadarisman, Yoskar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research aims to analyze juvenile criminal behavior with a focus on cases of assault and gang violence in the Legal Jurisdiction of Tampan Sub-District, Pekanbaru City. Youth criminality has become a primary concern in efforts to understand and address the social challenges faced by the community. This research employs a qualitative descriptive research method to explore the forms, motives, and causes of these acts of violence committed by the young individuals. The research subjects consist of 4 (four) juvenile informants involved in acts of violence and 1 (one) key informant. This research involves various methodological approaches, including literature review, in-depth interviews, and data analysis. Data will be collected from various sources, including police records, interviews with the involved juveniles, and interviews with authorized law enforcement personnel. The results of this research indicate a portrayal of the forms of violence carried out by juveniles, which can include assault and gang violence. There are various motives and causative factors for juveniles, both internal and external. Through a deeper understanding of this issue, it is expected to help create a safer society and protect young individuals involved in destructive criminal activities. Keywords: Youth, Criminal Behavior, Violence, Motives, Causes